Transcutaneous electrical acupoint stimulation (TEAS): Applications and challenges - Wen-lai ZHOU; Jing LI; Xiao-ning SHEN; Xia-tong HUA; Jing XIE; Yan-li ZHOU; Lu ZHU (World Journal of Acupuncture - Moxibustion)
Transcutaneous electrical acupoint stimulation (TEAS) is a kind of physical therapy that use electric current through the electrodes placed on the surface of acupoints to produce clinical effects in the human body, which is characterized by less adverse reaction and convenient operation. It has been widely used in the treatment of various diseases. This review introduces six major clinical applications of TEAS, named analgesia, regulation of gastrointestinal function, improvement of reproductive function, enhancement of cognitive function, promotion of limb function recovery and relief of fatigue. Besides, TEAS has been applied to the treatment of other chronic diseases such as hypertension and diabetes, achieving satisfactory clinical effects. However, two crucial challenges are encountered in the development of TEAS. One is the lack of standardization in the selection of parameters such as waveform, frequency, intensity and stimulation duration. The other is the limitation on the flexibility in the acupoint selection. This review analyzes key issues that need to be addressed in the current clinical application of TEAS, such as the selection of parameters and acupoints, and this review provides a certain reference value for optimizing regimens of TEAS and promoting its development and application.